Arthropod diversity indices in floricultural ecosystem: Which fares better? - RAMYA, R S; KUMAR, M GANESH; RANJITH, M; BAJYA, D R (The Indian Journal of Agricultural Sciences, 2021)
Biodiversity being a multidimensional property is always considered as tough to measure or quantify mostly because of the assortment of indices recommended for this purpose. However, there is no agreement about which indices are more appropriate and informative. Arthropods are one of the groups that have evaded the knowledge of human beings of their role in ecosystem function. We used data collected from floricultural ecosystems of rose, jasmine and cock’s comb fields during 2016 in Coimbatore, Tamil Nadu and calculated common arthropod diversity indices of species richness and species dominance in ordinal, familial and species level. The aim was to find out whether surrogacy is possible as far as arthropod diversity analyses are concerned and to determine whether some were better suited than others. In the present study, it was found that in most of the cases, irrespective of the index used, estimating species richness based on family level presented a closer picture to that of species level analysis, but could not totally replicate the sensitivity reflected by species level classification. Of the three dominance indices, only the Simpson's index discriminated the variation at all the three levels, viz. ordinal, familial and species with the discrimination being more pronounced at the species level. Hence, it could be inferred that the Simpson index could successfully be used in the floricultural ecosystems for estimating arthropod diversity based on dominance measures.